2002
DOI: 10.1199/tab.0024
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Transport and Homeostasis in Arabidopsis

Abstract: Phosphorus (P) is an essential macronutrient for all living organisms. It serves various basic biological functions as a structural element in nucleic acids and phospholipids, in energy metabolism, in the activation of metabolic intermediates, as a component in signal transduction cascades, and the regulation of enzymes.Of the major nutrients, P is the most dilute and the least mobile in soil. High sorbing capacity for P in the soil (e.g. sorbtion to metal oxides), P mineralization (e.g. calcium phosphates suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
255
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(268 citation statements)
references
References 150 publications
(177 reference statements)
5
255
0
8
Order By: Relevance
“…Phosphorus (P) is an essential macronutrient for all living organisms (Poirier and Bucher 2002). In plants, it is present both as a constituent of such compounds as nucleic acids, phospholipids and ATP.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus (P) is an essential macronutrient for all living organisms (Poirier and Bucher 2002). In plants, it is present both as a constituent of such compounds as nucleic acids, phospholipids and ATP.…”
Section: Introductionmentioning
confidence: 99%
“…Specific transport systems are essential for the uptake of Pi and for its partitioning within plants (Poirier and Bucher, 2002). Kinetic studies have shown the coexistence of two transport systems with low or high affinity for Pi (Dunlop et al, 1997;Misson et al, 2004;Miller et al, 2009).…”
mentioning
confidence: 99%
“…The primary source of P for plants is inorganic phosphate (Pi). Since Pi is often present in limited amounts in soils, it represents the second most frequently limiting factor for plant growth in a variety of natural ecosystems (Marschner, 1995;Poirier and Bucher, 2002;Misson et al, 2004). Pi concentration in the soil solution hardly reaches 1 mM in forest soils and may drop to micromolar or even submicromolar levels at the root-soil interface, where a depletion zone is generated by rapid Pi uptake of plants and rhizospheric microorganisms (Poirier and Bucher, 2002;Plassard and Dell, 2010).…”
mentioning
confidence: 99%
“…Vacuoles are the major storage compartment for Pi in the cell (storing about 80% of the total cellular Pi) in nonlimiting conditions (Bieleski, 1983;Poirier and Bucher, 2002). Pi incorporated in lipid membranes also represents an abundant and readily available source.…”
mentioning
confidence: 99%